Variasi dan Register Bahasa dalam Pengajaran Sosiolinguistik - sunahrowi sunahrowi (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Â Teaching sociolinguistics is so important since it involves at least two disciplines, i.e. social studies and lingusitics. Sociolinguistics is a study of language linking to social circumstance. There are so many varieties of social classification, such as sex, age, status and classes in collective life that rise so many languange variation. Language variation is usually influenced by at least three factors; geographical area that rise local dialect, social factors relating to social classes and status, and educational background. Those aspects develop social dialect and register. Keywords: Variation, Register, Sociolinguistics, and Teaching.